Percolation of Monte Carlo clusters - Wanzeller, W.G. [UNESP]; Cucchieri, A.; Mendes, T.; Krein, Gastão Inácio [UNESP] (Sociedade Brasileira de Física, 2004)
Percolation theory is of interest in problems of phase transitions in condensed matter physics, and in biology and chemistry. More recently, concepts of percolation theory have been invoked in studies of color deconfinement at high temperatures in Quantum Chromodynamics. In the present paper we briefly review the basic concept of percolation theory, exemplify its application to the Ising model, and present the arguments for a possible relevance of percolation theory to the problem of color deconfinement.